PROSEDUR PENYELESAIAN SENGKETA TANAH DI INDONESIA: TINJAUAN YURIDIS DAN PRAKTIS - ZULFIKAR, MUH REZA (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2025)
Land disputes are one of the most common legal issues in Indonesia, whether between individuals, communities and corporations, or communities and the government. The complexity of land issues is triggered by various factors, including limited land availability, overlapping certificates, unclear land rights status, and disharmony between customary law and positive law. This paper aims to describe the procedures for resolving land disputes in Indonesia through two main channels, namely non-litigation (mediation at the National Land Agency, arbitration, and customary mechanisms) and litigation (from district courts to the Supreme Court). The research method used is normative juridical with an approach based on legislation, cases, and doctrine. The results of the study show that the resolution of land disputes through non-litigation channels emphasizes restorative justice and efficiency, while litigation channels provide formal legal certainty through court decisions. The author concludes that strengthening land administration, digitizing certificates, and optimizing the role of mediation are very important to reduce the number of land disputes in the future.